AIRCRAFT BRAKE TEMPERATURE FROM A SAFETY POINT OF VIEW - Ján PIĽA; Peter KORBA; Michal HOVANEC (Scientific Journal of Silesian University of Technology. Series Transport)
Safety is critical throughout all stages of aircraft operation, from air mission to ground operation. One of the most important airframe systems that influences the efficacy of ground safety is a wheel brake system. Aircraft ground speed deceleration requires the dissipation of kinetic energy, which depends on aircraft weight and speed. Significant levels of aircraft kinetic energy must be dissipated in the form of heat energy. The brakes of heavy aircraft are especially prone to overheating during landing and taxiing on the ground. The aim of this paper is to focus on the dangers caused by aircraft brakes when overheating and ways in which to eliminate brake overheating problems from a safety perspective.